Small-scale, Community-Embedded Youth Justice Facilities: Lessons from Dutch Reforms and Recommendations for Cross-Jurisdictional Implementation - Souverein, Fleur (The prison journal, 2023)
Youth justice settings should provide safe, therapeutic environments, tailored to young people's needs. Current custodial models rarely meet these aims, mainly because a focus on security tends to outweigh an emphasis on care, diminishing rather than encouraging young people's positive development. This article reports on a three-year evaluation of youth justice reforms in the Netherlands, including small-scale, community-embedded facilities with an emphasis on relational security. We outline key operational elements and conditions for implementation of these facilities to provide guidance for youth justice professionals, and for managers and policymakers seeking to promote political and financial investments in effective youth justice strategies.